Kerukunan Umat Beragama di Desa Mopuya: Kajian Teologi Kerukunan Islam, Kristen, dan Hindu - Marcelina Priskila Pangkey (Universitas Negeri Medan, 2020)
This study aims to describe and analyze the values of religious harmony in the village of Mopuya. This paper, becomes a common reference as social capital, and can sustainably be the main foundation or foundation in caring for the harmony of inter-religious dialogue relations in Mopuya village, Bolaang Mongondouw. Through the relation of religious harmony, the social cohesion of the Mopuya community has so far been maintained. This research uses a qualitative-descriptive approach. Primary data were obtained through in-depth interviews with: village government, religious leaders, and elements of community institutions as representatives of each religion. The results of the analysis of the data obtained show that tolerance of religious harmony that has been applied so far, can be used as the main foundation of inter-religious dialogue relations in Mopuya village. Referring to the values of tolerance which is a pattern of community life as social capital, the Mopuya community is able to offer patterns of inter-religious relations that prioritize relational values. The relationship between religion that has been preserved by the Mopuya villagers shows a social relationship that maintains a peaceful and respectful pluralism.